Overwhelmed by the ’fama’ of the unseen Caesar: the rumours and the Caesar’s invasion in Italy in 49 B.C. - Belchior, Ygor Klain (Romanitas - Revista de Estudos Grecolatinos, 2019)
This article aims to study the influence of rumors during the advance of Caesar over Italy in the context of the civil wars against Pompey (49-48 BC). As we know, Caesar, have been crossed the Rubicon, was at a disadvantage and with fewer men, but still managed to conquer the peninsula by driving away his enemy. Our hypothesis is that such a victory was facilitated by the circulation of rumors about the fama of the victorious general and his troops. Intending to evaluate this influence of the rumors in this context, we studied the works of Lucanus, Cicero, Dio Cassio, Suetonius, Plutarch, Appian, and, of course, those of Caesar himself.